Evaluation Matrix for Assessing the Sustainability of Wall Panels for Rural India (Future Cities and Environment, 2025)
There is an increasing need for sustainable construction materials worldwide to reduce carbon emissions. Walling, being one of the most significant components of a building, has had various innovations and reinventions from traditional techniques. Although many sustainable alternatives exist for walling materials, they are mostly innovated for an urban context. An appropriate walling technique for a rural context remains challenging, as most often “one fits all” notion is applied in construction. Multiple parameters decide whether a material is suitable for a particular context, such as its technical, socio-economic and environmental characteristics. This paper reviews the various wall panels proposed for or used in rural areas as per identified parameters using the Multi-Criteria Decision-Making method of TOPSIS. The panels are ranked based on their suitability for the rural context of India. The study indicates that the Ekra wall panels are most appropriate, followed by the CSEB technique. This system aids stakeholders in selecting sustainable and appropriate walling systems and making informed choices suitable for their contexts.